Serious Complications for Patients, Care Providers and Policy Makers: Tackling the Structural Violence of First Nations People Living with Diabetes in Canada - Maar, Marion A, Dr.; Manitowabi, Darrel; Gzik, Danusia; McGregor, Lorrilee; Corbiere, Cheri (International Indigenous Policy Journal, 2011)
Type 2 diabetes mellitus is a progressive metabolic disorder that affects Aboriginal people disproportionately around the world. Evidence shows that diabetes treatment strategies can effectively reduce complications related to the disease; in contrast many Aboriginal people develop these rapidly and at a young age. We conducted qualitative research on the barriers to evidence-based self-management behaviours and education from the perspectives of Aboriginal people living with type 2 diabetes and their health care providers on Manitoulin Island in Ontario, Canada. Applying the concept of structural violence, we analyzed the social and political arrangements that can put Aboriginal people with diabetes “in harm’s way” by interfering with diabetes management. Lastly, we provide recommendations for structural interventions.